Arabic grammar: the role of the grammatical government in interpreting vowel and semantic changes - Yaacob, Solehah@Nik Najah Fadilah (2014)
The Research Focuses On The Role Of The Grammatical Government In Interpreting Vowel And Semantic Changes In Arabic Grammar In Explaining The Semantic Changes Resulting From Phonetic Changes, Especially In Respect To Vowels. It Further Looks Into The Factors Which Contribute To Such Changes In Phonetics And Evaluates The Significance Of The Altered Meanings In The Field Of Semantics.